1995
DOI: 10.1111/j.1600-051x.1995.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline‐resistant micro‐organisms recovered from patients with refractory periodontal disease

Abstract: Tetracycline in combination with scaling and root planing is frequently used to treat refractory periodontal disease. This study examined tetracycline resistance in bacteria recovered from periodontal pockets of patients with refractory periodontitis. Bacterial isolates resistant to 10 micrograms/ml of tetracycline were isolated from plaque samples of 17 patients, of whom 6 had received tetracycline within 8 weeks prior to sampling. Minimal inhibitory concentrations (MICs) of tetracycline and minocycline were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 31 publications
4
33
0
2
Order By: Relevance
“…The tet (M) determinant is commonly found in some subgingival species considered "beneficial" such as oral streptococci, Veillonella and Actinomyces spp. 74,104,105,121 . Lacroix and Walker 74 (1995) subcultured and identified 204 tetracycline-resistant strains from 68 patients with chronic periodontitis.…”
Section: Mechanism Of Action and Resistancementioning
confidence: 99%
“…The tet (M) determinant is commonly found in some subgingival species considered "beneficial" such as oral streptococci, Veillonella and Actinomyces spp. 74,104,105,121 . Lacroix and Walker 74 (1995) subcultured and identified 204 tetracycline-resistant strains from 68 patients with chronic periodontitis.…”
Section: Mechanism Of Action and Resistancementioning
confidence: 99%
“…Several studies have shown that tetracyclines are active against A. actinomycetemcomitans (15,17,23). Tetracyclines are extensively used as adjuncts in the treatment of periodontitis, a disease affecting the tooth-supporting tissues (gingiva, periodontal ligament, and alveolar bone) and resulting in tooth loss (21,23).…”
mentioning
confidence: 99%
“…; Olsvik, 1995). Strains GF10, MK1, UM3 and W1219 T were isolated from periodontal pockets and W2274 was isolated from a dentoalveolar abscess.…”
mentioning
confidence: 99%